An improved fluorescent tag and its nanobodies for membrane protein expression, stability assay, and purification - Hongmin Cai (Nature Portfolio, 2020)
In this work, the authors demonstrate that a coral thermostable GFP (TGP) is an improved tag compared to conventional GFPs. In addition to reporting melting point stability at temperatures near 90 °C, its fusion also helps increase expression levels of test membrane proteins. They further generated synthetic nanobodies against TGP to facilitate purification.